Humanização no parto e nascimento: caminhos e estratégias de cuidado de um serviço referência em humanização - Aryanne Gabrielle Policarpo (2021)
ABSTRACT Introduction: The humanization of childbirth and birth have been the master line, a path to transition from the traditional and medicalized model to a humanized model that respects the uniqueness of women and promotes their protagonist. For this paradigm shift, much has been discussed about humanization in the process of childbirth and birth, which aims to provide assistance based on the principles of SUS, aiming to overcome obstetric violence. Objectives: Analyze the humanization of care during the childbirth and birth process under the perception of the women, comprehend the care strategies implemented by a maternity reference for the humanization of childbirth and birth, under the perception of women and service management. Methodology: This is a multicenter, descriptive study of qualitative approach, which used as a theoretical framework the National Humanization Policy (PNH), carried out in a reference maternity hospital for the humanization of childbirth and birth of the municipality of Belo Horizonte, Brazil. 11 women and a representative of hospital management were interviewed, from September to November 2020, through semi-interview structured. The interviews were recorded and transcribed in full, submitted to analysis content and categorization. The study was approved by the Research Ethics Committee of UFMG and Sofia Feldman Hospital and followed the ethical and legal principles guiding research involving human beings. Results: The analysis of the data resulted in two categories: “Humanization as a concrete care experience” and “Strategies of care implemented by the service for the humanization of childbirth and birth”. At the perception of the women, the care received in the process of childbirth and birth appears in the light of the PNH, in the following guidelines: welcoming atmosphere, expanded clinic and shared and users’ rights. The study was observed the satisfaction of women in relation to the care received and the practices implemented by the service as a guarantee of comprehensive assistance to women. Quality care based on evidence reflects directly on the process of childbirth and birth. Conclusion: The care strategies implemented by the service for the humanization of childbirth and birth is directly related to the satisfaction of women in the birth process and add quality to this process. Listen to women's reports and understand how they experience the implemented care is a way that can help other professionals, managers to follow the path of humanization, which is far beyond evidence-based practices.